Stable Isotope Records and Mg/Ca Ratios of the RAT Speleothem from Menorca Island (387–209 ka) - Judit Torner; Isabel Cacho; Heather M Stoll; Ana Moreno; Joan O Grimalt; Francisco Javier Sierro; Joan J Fornós; Hai Cheng; R Lawrence Edwards (PANGAEA, 2025)
This dataset comprises speleothem carbon and oxygen isotope records, Mg/Ca ratios results from the RAT speleothem. The data were used to reconstruct past climate variability in the western Mediterranean region over the interval 387 to 209 ka, encompassing several glacial terminations (TIV, TIII, and TIIIa). The speleothem was collected in winter 2011 from Murada Cave, located on Menorca Island (39°57'58''N; 3°57'53''E). Stable isotope analyses (δ^1^3C and δ^1?O) were performed with 500.167emμg of carbonate powder using isotope ratio mass spectrometry (IRMS), and Mg/Ca ratios were measured by inductively coupled plasma mass spectrometry (ICP-MS) at the Scientific and Technological Centres of the University of Barcelona. Analytical uncertainties were ≤ 0.04 extperthousand VPDB for δ^1^3C and ≤ 0.08 extperthousand VPDB for δ^1?O, NBS19 international standard (Coplen, 1996) was used for calibration.